Likelihood of Smoking Among Cancer Survivors: An Updated Health Information National Trends Survey Analysis. Issue 12 (7th March 2019) - Swoboda, Christine M; Walker, Daniel M; Huerta, Timothy R
Abstract: Introduction: Cancer survivors are at high risk for cancer reoccurrence, highlighting the importance of managing behavioral risk factors for cancer. Despite this risk, many cancer survivors continue to smoke cigarettes. This article describes the relationship between smoking behavior and demographic and clinical factors in cancer survivors. Methods: Multinomial logistic regression of cross-sectional data from the Health Information National Trends Survey was conducted using combined data from years 2003, 2005, 2007, 2011, 2012, 2013, and 2014. Independent variables included age, cancer history, race, education level, marital status, insurance status, and data year; the dependent variable was smoking status (current vs. former or never). Results: Cancer survivors were less likely to be current smokers but more likely to be former smokers than those with no history of cancer. Cancer survivors that currently smoked were more likely to have lower education levels, be divorced, separated, or single, or not have health insurance. Older cancer survivors, Hispanic, and non-Hispanic black survivors were less likely to smoke. Among cancer subgroups, prostate cancer survivors had the lowest rate (8.8%) of current smoking from 2011 to 2014, and cervical cancer survivors had the highest rate (31.1%). Conclusions: Although those with no history of cancer had higher rates of current smoking, many subgroups of cancer survivors continued to smoke at higher rates than average cancer survivors. Cancer survivors that were younger, had lower education levels, were any marital status other than married or widowed, were uninsured, or survived cervical cancer were more likely to be smokers than other survivors. Implications: It is important to understand which types of cancer survivors are at high risk of continued smoking to better inform tobacco dependence treatment interventions among those at high risk of cancer reoccurrence. Our findings suggest targeted tobacco dependence treatment efforts among cancer survivors should focus on survivors of cervical cancer and survivors that are young, unmarried, uninsured, or have lower education levels.